The Influence of Prior Knowledge on Physics Learning Outcomes using Structured Quizzes - Ummah, Rakhmatul; Raden Oktova (INOVASIA, 2024)
Educator believe that prior knowledge can facilitate students in comprehending subsequent materials and serve as an indicator of learning outcomes. This study aims to explore the learning outcomes of advanced class physics students based on their prior knowledge, using structured quizzes as a measuring tool. The influence of prior knowledge on learning outcomes was quantified using SPSS, revealing a relative contribution of 34.62% to learning outcomes, with an effective contribution of 51%. Consequently, it can be concluded that the level of prior knowledge significantly affects learning outcomes.